(untitled) (Journal of Oriental Studies, 2016)
In this paper is proposed a method of teaching oral speech as a priority. As proof of this, we note that since the primary function of language is a communicative function, it is quite legitimate claim. Teaching of oral speech is truly one of the most important elements in learning languages, especially Korean, because Korean language is replete with numerous grammatical constructions and vocabulary, which are clearly delineated in writing and oral speech. That is what constitutes the main difficulty in teaching oral speech in Korean.